2021
DOI: 10.1111/nan.12693
|View full text |Cite
|
Sign up to set email alerts
|

Seizure activity and brain damage in a model of focal non‐convulsive status epilepticus

Abstract: Aims: Focal non-convulsive status epilepticus (FncSE) is a common emergency condition that may present as the first epileptic manifestation. In recent years, it has become increasingly clear that de novo FncSE should be promptly treated to improve post-status outcome. Whether seizure activity occurring during the course of the FncSE contributes to ensuing brain damage has not been demonstrated unequivocally and is here addressed. Methods: We used continuous video-EEG monitoring to characterise an acute experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…44 Both proinflammatory cytokines and chemokines released by a-PBMCs and hALB extravasation promote resident microglia activation, 45 which in turn are expected to activate astrocytes and exacerbate reactive pathways. 10 In our experiments, microgliosis was evident when either ConA-activated hPBMCs or a-hPBMC supernatant only (both associated with LPS and hALB infusion) were perfused into the in vitro guinea pig brain. Glial cells have a plethora of housekeeping functions such as sensing and responding to alterations in energy supply, neuronal activity, extracellular ion concentrations, osmolarity, among many other processes.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…44 Both proinflammatory cytokines and chemokines released by a-PBMCs and hALB extravasation promote resident microglia activation, 45 which in turn are expected to activate astrocytes and exacerbate reactive pathways. 10 In our experiments, microgliosis was evident when either ConA-activated hPBMCs or a-hPBMC supernatant only (both associated with LPS and hALB infusion) were perfused into the in vitro guinea pig brain. Glial cells have a plethora of housekeeping functions such as sensing and responding to alterations in energy supply, neuronal activity, extracellular ion concentrations, osmolarity, among many other processes.…”
Section: Discussionmentioning
confidence: 50%
“…We observed that microglial cells responded promptly to these immunological triggers through a significant change in their morphological phenotype toward a more activated state demonstrated by their amoeboid shape 44 . Both proinflammatory cytokines and chemokines released by a‐PBMCs and hALB extravasation promote resident microglia activation, 45 which in turn are expected to activate astrocytes and exacerbate reactive pathways 10 . In our experiments, microgliosis was evident when either ConA‐activated hPBMCs or a‐hPBMC supernatant only (both associated with LPS and hALB infusion) were perfused into the in vitro guinea pig brain.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Since this is critical information necessary for comparing BBB function among the Ctrl and subjects with SZ, we have developed a semi-quantitative protocol using the Cavalieri estimator stereological function in Stereo Investigator software (MBF Bioscience, VT, United States). Similar to previous studies, our semi-quantitative protocol relies on the immunoreactivity demonstrated by the extravasated IgGs with neurons and neuropil ( Librizzi et al, 2021 ; Vila Verde et al, 2021 ). The Cavalieri estimator method is a proven unbiased stereological method used to calculate areas in tissue sections, and we have adopted it to estimate IgG leaked area fraction or the extent of BBB leak ( Cohen, 1992 ; No authors, 2021 ).…”
Section: Methodsmentioning
confidence: 92%